Two Masters in Baglama Performance, One Folk Song: The Example of Nida Tüfekçi/Arif Sağ He has learnt his lesson and is now paying the price". - Türkay, Mehmet Kürşad (Electronic Turkish Studies)
This study presents a comparative analysis of the bağlama and vocal performances of Nida Tüfekçi and Arif Sağ, two prominent figures in the tradition of Turkish folk music, from technical, aesthetic, and interpretative perspectives. The research aims to examine how traditional performance styles are reinterpreted through individual attitudes and personal performance practices within the framework of folk music tradition. In this context, the study contributes to understanding the continuity and transformation of performance practices in Turkish folk music. As influential figures in the transmission and development of the folk music repertoire, both artists have made distinctive contributions to the bağlama tradition through their performance approaches shaped by different historical and cultural contexts. While Nida Tüfekçi stands out with a performance style that preserves the simplicity, naturalness, and local character of the Central Anatolian tradition, Arif Sağ incorporates modern musical approaches into folk music performance, positioning the bağlama as an instrument with universal expressive potential. The song "Dersini Almış da Ediyor Ezber," belonging to the Yozgat region and categorized within Sürmeli variants, was selected as the sample of the study. Performance recordings of both artists were transcribed into musical notation and analyzed comparatively in terms of technique, ornamentation, rhythmic structure, and stylistic features. In addition to his role as a performer, Nida Tüfekçi has made significant contributions to Turkish folk music as a compiler, particularly in the context of Yozgat regional music and Sürmeli performance practices. Arif Sağ, on the other hand, is not only a master performer of regional styles but also a key figure in the transmission of these practices through his master–apprentice relationship with Tüfekçi. The findings indicate that Tüfekçi’s approach represents a model of traditional representation, whereas Sağ’s performance style reflects a synthetic and innovative interpretation. These two approaches are shown to complement each other within the continuity of Turkish folk music performance tradition. The study highlights the significance of regional styles and individual performance attitudes in shaping musical expression and contributes to performance-based research in ethnomusicology.